(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine the effects of Blended Learning on Grade 1 Pupils of San Gabriel Elementary School during this COVID-19 pandemic. The COVID-19 pandemic is expected to have a long-term adverse effect on the world economy (World Bank Group, 2020). It affects almost every aspect of human life, including the educational system. It affects all academic institutions, replacing F2F with blended learning (BL), which incorporates distance learning and online classes, and this has affected teaching and learning globally. This study was carried out for numerous reasons in this circumstance. Researchers aimed to learn more about the effects of BL as distance learning supplemented by elearning in this pandemic, aimed to discover if the BL strategy positively promotes learning in the same way as traditional techniques and if the deployment of blended learning affects student academic success. We also want to showcase Blended learning positives to counter its flaws. The researchers utilized the descriptive method with the support of mixed qualitative and quantitative research methods or the mixed-method approach in determining the effects of blended learning on grade 1 pupils of San Gabriel Elementary School. Simple random sampling is used to determine the respondents of fifteen (15) grade 1 teachers of San Gabriel Elementary School.